The islamic economic journal Prinsip Dasar Rancang Bangun Ekonomi Islam - Linggawati Widyan (Program Studi Ekonomi Syariah dengan Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Institut Pesantren Sunan Drajat Lamongan, 2022)
This article discusses how to formulate an Islamic economic design and the principles that form the basis of the economy. By understanding the design of the Islamic economy, it is hoped that you can get a complete and comprehensive picture in a nutshell about the Islamic economy which is composed of the roof, pillars and foundation. Although Islamic economics has several differences in its structure and sequence, in substance it is not much different, it is superior to other economies. There are basic principles in the design of Islamic economics. Some of these principles can generally be divided into three parts, namely: universal values, derivative principles and morals. Islamic economics is built on five universal Islamic values which are considered the foundations of Islamic economics including: ilahiyah, al-adl, an-nubuwah, al-khalifa and al-ma'ad. Then the derivative principles act as a pillar and consists of three principles including: multiple ownership, freedom to act and social justice. The last roof of the building is morals. Each of these parts forms a building and becomes a principle that can be used as an aspiration to formulate various theories in Islamic economics.